Komodifikasi Budaya dalam Challenge TikTok sebagai Strategi Representasi Identitas di Era Media Sosial - Putri Aulia Febrianda; Mirza Azkia Muhammad Adiba (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study aims to analyze the commodification of social media through the lens of Jean Baudrillard’s theory of simulation and simulacra, using TikTok Indonesia as a case study. In the digital era marked by hyperreality, social media has evolved beyond a platform for interaction to become a space of symbolic production and consumption. Representations in digital content often replace reality itself, constructing idealized and aestheticized images driven by algorithmic appeal. Employing a qualitative descriptive approach and case study method, this research observes several popular TikTok contents in Indonesia, focusing on self-branding, daily life aesthetics, and cultural challenges. The findings reveal that most of the content represents simulations of life that emphasize visual impact over authentic representation. Personal identity, cultural elements, and even private emotions are transformed into digital commodities with social and economic value manifested through likes, comments, followers, and potential endorsements. The study concludes that TikTok serves as a site for the construction of new meanings where social reality is increasingly redefined through symbolic consumption. Rather than reflecting genuine life experiences, digital content tends to follow trends and visuals that satisfy the logic of visibility and viral appeal. These findings reinforce Baudrillard’s argument that in postmodern society, reality is no longer directly experienced, but is instead replaced by institutionalized and mass-reproduced representations shaped by media systems and consumer culture.